Analisis Diksi dan Tipografi pada puisi “Tragedi Winka dan Sihka” Karya Sutardji Calzoum Bachri - Arneta Destria Kirana (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2022)
This study discusses the use of Diction and Typography in the poem "Tragedi Winka dan Sihka" your poem uses a qualitative descriptive research method with a stylistic approach. The poem "Tragedy of Winka and Sihka" discusses the storyline of life in a marriage which does not always go well but in a married life there will be trials. Of every word that certainly contains some very interesting meanings. This study aims to explain Diction and Typography in the poem "Tragedi Winka and Sihka".